2003
DOI: 10.1034/j.1600-0420.2003.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of 0.1% olopatadine hydrochloride and 0.5% ketorolac tromethamine in the treatment of seasonal allergic conjunctivitis

Abstract: ABSTRACT.Purpose: To compare the therapeutic effects of two ophthalmic solutions (0.1% olopatadine hydrochloride and 0.5% ketorolac tromethamine) with different pharmacological mechanisms on the clinical signs and Symptoms of seasonal allergic conjunctivitis (SAC). Methods: Forty patients with the signs and symptoms of SAC (i.e. hyperaemia, itching, mucus discharge, tearing) were included in this placebo-controlled, randomized, parallel group, single centre study. In group 1 (20 patients) one eye of each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…All patients were recruited in the study in May 2013, during the peak spring allergy season in Turkey (Yaylali et al 2003), and evaluated at the Mevlana University eye clinic. Patients with a history of SAC of ≥2 years' duration, with moderate or severe signs and symptoms of clinically active allergic conjunctivitis (conjunctival hyperaemia, itching, tearing, chemosis or lid oedema) and a positive skin prick test to at least one antigen common in the geographical area were included in the SAC group.…”
Section: Study Populationmentioning
confidence: 99%
“…All patients were recruited in the study in May 2013, during the peak spring allergy season in Turkey (Yaylali et al 2003), and evaluated at the Mevlana University eye clinic. Patients with a history of SAC of ≥2 years' duration, with moderate or severe signs and symptoms of clinically active allergic conjunctivitis (conjunctival hyperaemia, itching, tearing, chemosis or lid oedema) and a positive skin prick test to at least one antigen common in the geographical area were included in the SAC group.…”
Section: Study Populationmentioning
confidence: 99%
“…In allergic conjunctivitis diclofenac and ketorolac were similar in relieving the symptoms particularly itching, and some studies have shown superiority of ketorolac in relieving ocular itching. 14,4,9,15 The efficacy of topical NSAIDs particularly ketorolac in relieving ocular itching is probably related to the decreased synthesis of pruritogenic PGs-PGE-2 and PGI-2. 4 In several other studies ketorolac was found to be most effective among the topical NSAIDs in relieving ocular symptoms, particularly itching.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data, ocular and medical history, concomitant medications, physical examination, clinical examination including recording of vital signs, ophthalmological examination (ocular sign and symptom score) and details of drug prescription were recorded in the study proforma at baseline visit (visit 1) and all subsequent follow-up visits. [10][11][12][13] Follow-up visits were done on day 8 (visit 2) and day 15 (visit 3) after administering the study drugs. A deviation of ±1 day for first follow-up and ±2 days for subsequent follow-up was accepted.…”
Section: Methodsmentioning
confidence: 99%